STRATEGI GURU DALAM PENGEMBANGAN SIKAP TOLERANSI SISWA SEKOLAH DASAR MELALUI PEMBELAJARAN KEBERAGAMAN BUDAYA - Septi Amalia; Husna Farhana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study analyzes teachers’ strategies in developing elementary school students’ tolerance attitudes through cultural diversity learning. The problem addressed is the limited understanding of diversity and the persistence of intolerant behaviors among students, highlighting the need for early character education. The purpose of this research is to identify effective strategies used by teachers to foster tolerance in elementary schools. This study employed a systematic literature review by examining ten relevant journal articles published between 2018 and 2025. Data were analyzed using content analysis techniques, including theme identification and synthesis of findings. The results indicate that dialogic discussions, cooperative learning, teacher modeling, habituation, and culture-based project learning are effective in strengthening students’ understanding, empathy, and inclusive attitudes. Consistent implementation and supportive classroom environments are key factors in successfully developing tolerance attitudes.